2021
DOI: 10.1038/s41467-021-25205-2
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar release of rDNA repeats for repair involves SUMO-mediated untethering by the Cdc48/p97 segregase

Abstract: Ribosomal RNA genes (rDNA) are highly unstable and susceptible to rearrangement due to their repetitive nature and active transcriptional status. Sequestration of rDNA in the nucleolus suppresses uncontrolled recombination. However, broken repeats must be first released to the nucleoplasm to allow repair by homologous recombination. Nucleolar release of broken rDNA repeats is conserved from yeast to humans, but the underlying molecular mechanisms are currently unknown. Here we show that DNA damage induces phos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 76 publications
(143 reference statements)
0
18
0
Order By: Relevance
“…In both fission yeast and budding yeast, it has been demonstrated that Ufd1 not only has the ability to bind ubiquitin but also, via a SIM in its C-terminus, bind SUMO. This appears to facilitate the function of Ufd1 in STUbL mediated genome stability processes (Bergink et al, 2013;Capella et al, 2021;Kohler et al, 2015;Nie et al, 2012;Nie and Boddy, 2016). While we cannot exclude the possibility that SUMO-ubiquitin hybrid chains play a role in arsenic-induced degradation of PML and PML-RARA, the SIM present in the C-terminus of yeast Ufd1 is not present in the human form of UFD1, suggesting that SUMO recognition by Ufd1 is not required in arsenic-induced p97 mediated extraction of PML from nuclear bodies.…”
mentioning
confidence: 99%
“…In both fission yeast and budding yeast, it has been demonstrated that Ufd1 not only has the ability to bind ubiquitin but also, via a SIM in its C-terminus, bind SUMO. This appears to facilitate the function of Ufd1 in STUbL mediated genome stability processes (Bergink et al, 2013;Capella et al, 2021;Kohler et al, 2015;Nie et al, 2012;Nie and Boddy, 2016). While we cannot exclude the possibility that SUMO-ubiquitin hybrid chains play a role in arsenic-induced degradation of PML and PML-RARA, the SIM present in the C-terminus of yeast Ufd1 is not present in the human form of UFD1, suggesting that SUMO recognition by Ufd1 is not required in arsenic-induced p97 mediated extraction of PML from nuclear bodies.…”
mentioning
confidence: 99%
“…Then, poly-sumoylated EME1 is extracted by the AAA ATPase VCP/p97-NPL4-UFD1 complex, which we observed in our EME1-IP (Extended Data Fig. 7) and which is established to extract poly-sumoylated and/or ubiquitinated proteins form replication forks and nucleolar repair condensates [49][50][51][52] . This step likely requires poly-sumoylation-dependent ubiquitination, as it best understood for the STUbL RNF4 but may also apply to TRIM25.…”
Section: Discussionmentioning
confidence: 99%
“…CoIP assays were performed following a previously described protocol 70 with a few modifications in the lysis buffer. The lysis buffer contained 50 mM HEPES pH 7.4, 100 mM NaCl, 10% glycerol, 1 mM EDTA pH 8, 2.5 mM MgCl 2 , 0.5% NP-40, 1× complete EDTA-free protease inhibitor cocktail (Roche), 2 mM PMSF (Serva), 20 mM N -ethylmaleimide (NEM, Sigma).…”
Section: Methodsmentioning
confidence: 99%